OPTIMALISASI KEPADATAN BENIH IKAN MAS (Cyprinus carpio) STRAIN RAJADANU PADA PENDEDERAN DI KOLAM AIR TENANG [Density Optimization of Carp Seed (Cyprinus carpio) Strain Rajadanu in the Nursery in Calm Pool Water] - Radona, Deni; Asih, Sidi; Huwoyon, Gleni Hasan (BERITA BIOLOGI, 2012)
National fisheries production is not proportional to the increase of the population now, so that the consumption of animal protein needs are not met.For the sake of national fisheries production there is a need for intensive cultivation technology breakthroughs to spur the density in nursery phase ârajadanuâ carp (Cyprinus carpio) strain. This experiment aim to determine the appropriate density of rajadanu carp growth in the pond at the nursery phase. The average length of tested fishes is 2.02 cm and the average initial weight is 0.25 g maintained in the out door plot pool of Research Installation for Germ Plasm of the Research and Development Division of Freshwater Fisheries, Cijeruk, Bogor measuring 1x1x1 m with density 100, 150 and 200 fishes/m3 .Each treatment was repeated 3 times. Feed used was a commercial feed containing 28% protein given in 2 times a day as much as 5% of the total weight of fish. The results showed that after 40 days, each treatment showed no significant difference (P> 0.05) with absolute length and weight growth of the absolute highest in nursery density of 200 fishes/m3 of 1.30 Â± 0.10 cm and 1.14 Â± 0, 18 cm with a daily growth rate of 1.30 Â± 0.10% and 4.08 Â± 0.55%, and the highest survival at densities 200 fishes/m3 of 92.5 Â± 6.55%.